The Psychology of Diplomacy in the Palestinian-Israeli Conflict: The Role of Emotions and Perceptions in Peace Negotiations - Octavian, Tomy; Noviyana, Linda (Journal Of Middle East and Islamic Studies, 2026)
The Palestinian-Israeli conflict remains one of the major challenges in building sustainable peace through diplomacy. This study analyzes the role of emotions and perceptions in Palestinian-Israeli peace negotiations through the perspective of diplomacy psychology. Using an integrative literature review and an integrated theory approach that combines psychological theories and international relations theories, this study synthesizes empirical and conceptual findings on the Palestinian-Israeli peace negotiation process. The results of the analysis show that negative emotions such as fear, hatred, and anger worsen diplomatic relations and hinder peace deals. Distorted perceptions of the other side's intentions and identities, as well as conflicting historical narratives, reinforce distrust and resistance to compromise. A strong national identity also complicates the negotiation process. These findings underscore the importance of managing emotions, improving perceptions, and respecting national identity. The practical implication is that international mediators need to pay more attention to psychological and social dynamics in designing sustainable peace strategies.